A Report of Zika Virus Seroprevalence in Republic of the Congo - (:unkn) unknown (My University, 2019)
Zika virus (ZIKV) is an arthropod-borne RNA virus (arbovirus), belonging to the Spondweni serogroup. ZIKV was first described in Africa in 1947 and remained sporadic until Micronesia outbreak in 2007, which was followed by outbreaks in the Pacific Islands, Latin America, and the Caribbean. Subsequent to the epidemics, ZIKV revealed its severity as virus was sexually transmissible, and it was associated with serious fetal and neurological complications. ZIKV originated from Africa; however, little is known about the epidemiology of the virus in African populations. Following a recent study in Cameroon that evidenced low ZIKV epidemiology associated with a presumptive (peri-)sylvatic transmission, we performed a seroepidemiological study in Republic of the Congo, neighbor of Cameroon. To accomplish this, 386 serum specimens from volunteer blood donors collected in 2011 from rural and urban areas of Republic of the Congo were tested with ZIKV-specific methodology; primary screening with anti-NS1 ZIKV IgG ELISA followed by confirmation with cytopathic effect (CPE)-based virus neutralization test (VNT). ZIKV seropositivity was determined as low as 1.8%, varying slightly between urban and rural areas (1.7% and 3.6%). These results demonstrate that the majority of the population of Republic of the Congo is immunologically naïve against ZIKV with a presumptive (peri-)sylvatic transmission cycle, which emphasizes the importance of surveillance studies in Africa.
Keywords: African Research